Examining the legal protection of social and economic rights of children in Nigeria (2013)
This paper begins with an examination of sociological conditions in Nigeria, followed by a review ofthe traditional arguments of the adoption of a rigid Classification of social and economic rights which puts them, by definition into positive rights. It then examines the socio- economic rights obligated under the Convention on the Rights of the Child (CRC), African Charter on the Rights and Welfare ofthe Child (ACRWC) the African Charter on Human and Peoples' Rights (ACHPR) and the International Covenant on Social and Economic and Cultural Rights (IECSCR). The paper then examines and analyses the domestic frameworks for the Implementation of social and economic rights of children. It argues that the government's refusal to consider social and economic rights as justiciable rights amounts to a deprivation of the safeguards obligated by the international treaties to which children in Nigeria are entitled. The paper discusses that the enforcement of social and economic rights depends both on the language of constitutional rights and the willingness of the judiciary to review the constitutionality of legal rules related to social rights. The paper illustrates that courts in some jurisdictions such as India and South Africa have found ways of protecting social rights either directly, through determining the minimum content of a right, or indirectly, through other rights that are justiciable. A comparative analysis with other jurisdictions is carried out to support this assertion. A comparative jurisprudence is instructive in order to guide the state, so that it can draw examples from other jurisdictions. White noting that in Nigeria there is a lack of a judicial tradition of enforcing social and economic rights, it demonstrates that judges in India and South Africa are generally receptive to injunctive and precautionary procedures in urgent socio-economic rights cases. The purpose of this paper is to develop a more precise understanding of the noture of the state's obligations concerning social and economic rights of children in Nigeria. The central outcome of the paper are twofold; first it sheds light on the existing realities about the protection of socio-economic rights o; children in Nigeria with the hope that at the end of the expose a solution will be proffered that might be considered by future policy makers. Second, it shows the urgency for protection and Provision of basic necessities of life for children. The paper concludes that the protection of social and economic rights of children in Nigeria is inadequate